Inhibition of the Caveolin-1 pathway promotes apoptosis and overcomes pan-tyrosine kinase inhibitor resistance in hepatocellular carcinoma - Tasnuva D. Kabir; Samuel Beck; Lisa M. Stuart; Ji Li; Rui Hou; Peiwen Liu; Shelby Margolius; Claire Kim; Yu Suk Choi; Edward R. Bastow; Dianne J. Beveridge; Lisa Spalding; et al. (Cell Death and Disease)
Abstract Resistance to multi-tyrosine kinase inhibitors (TKI) is a major clinical concern in advanced hepatocellular carcinoma (HCC). Herein, we aimed to uncover the mechanisms underlying pan-TKI resistance and to identify potential therapeutic targets. We used multiple TKI-resistant HCC cell lines to identify caveolin-1 (CAV1) as a key driver of therapeutic resistance. CAV1 downregulation induced apoptosis, inhibited metastasis and restored TKI sensitivity in both inherent and acquired TKI-resistant HCC cells. Mechanistically, in acquired TKI-resistant cells aberrant CAV1/STAT3/P70S6K signalling is required for their survival, motility, and invasiveness. CAV1 inhibition reduced expression of dormancy regulators E-cadherin, RAC1 and p21, enhanced cancer stemness markers, and disrupted downstream STAT3/P70S6K and AMPKα signalling pathways, prompting cancer cells to exit from dormancy and initiate autophagy-induced cell death. Furthermore, selective inhibition of AXL and FGFR4 downstream of the CAV1 pathway sensitized TKI-resistant cells to sorafenib and lenvatinib, respectively. In addition, microRNA-7-5p (miR-7) was identified as an endogenous regulator of CAV1; and miR-7’s inhibitory effect on CAV1 and FGFR4 suppressed the STAT3/P70S6K pathway, promoted autophagy and triggered apoptosis in lenvatinib-resistant cells. Combination therapy using either lenvatinib or sorafenib and selective CAV1 inhibitors (e.g., siCAV1/miR-7), or AXL/FGFR4 inhibitors (e.g., BGB324/BLU9931) effectively overcame pan-TKI resistance. In HCC patient datasets, elevated CAV1 mRNA was observed in sorafenib non-responders, and single cell RNA-sequencing of HCC patient tumours revealed a rare population of CAV1+ cancer cells associated with recurrence. High CAV1 expression was specific to HBV+ HCC patients and independently predicted poor survival. Further, targeting of CAV1, AXL or FGFR4 effectively overcame TKI resistance in HCC patient derived organoids (PDOs). Our findings highlight a previously unrecognized role for CAV1-driven signalling in sustaining tumour dormancy, a critical and challenging therapeutic barrier underlying recurrence and pan-TKI resistance in HCC. Therapeutically targeting these pathways offer a promising and novel strategy to eliminate dormant tumour cells, thereby overcoming resistance and improving treatment outcomes.